OCCURRENCE OF TYLOTOTRITON VERRUCOSUS ANDERSON IN MANIPUR - SINGH, P. MUNAL; DEVI, P. BIJAYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
This paper embodies the finding of a preliminary survey on the occurrence o Tylototriton verrucosus Anderson, Ukhrul District of Manipur. A brief description of the specimen studied have been acknowledged in tihis paper.